Time-encoded pseudocontinuous arterial spin labeling: Basic properties and timing strategies for human applications - Teeuwisse, Wouter M.; Schmid, Sophie; Ghariq, Eidrees; Veer, Ilya M.; van Osch, Matthias J.P. (Magnetic resonance in medicine, 2014)
Purpose In this study, the basic properties and requirements of time‐encoded pseudocontinuous arterial spin labeling (te‐pCASL) are investigated. Also, the extra degree of freedom delivered by changing block durations is explored. Methods First, the minimal duration of encoding blocks, the influence of cardiac triggering, and the effect of dividing the labeling period into blocks are evaluated. Two new strategies for timing the encoding blocks in te‐pCASL are introduced: variable block duration to compensate for T1‐decay and the free lunch approach that uses the postlabeling delay time that is idle in standard pCASL to acquire arterial transit time (ATT) information. Simulations are used to probe possible signal losses. Results No signal loss was found when dividing the labeling period into blocks with duration >50 ms. In time‐encoded perfusion imaging, no cardiac triggering is required. Summation of results for individual blocks in te‐pCASL postprocessing causes severe loss of temporal SNR. Quality of cerebral blood flow (CBF) maps was not affected by the encoding line order. Conclusion Adjusting the timing of encoding blocks in te‐pCASL allows for tailoring the acquisition to specific applications. With the free lunch setup, te‐pCASL delivers CBF and high resolution ATT maps within a single scan, with a small penalty in tSNR. Magn Reson Med 72:1712–1722, 2014. © 2014 Wiley Periodicals, Inc.